ГУМАНІТАРИЗАЦІЯ ВИЩОЇ ТЕХНІЧНОЇ ОСВІТИ: ПСИХОЛОГО-ПЕДАГОГІЧНИЙ АСПЕКТ (Педагогіка вищої та середньої школи, 2022)
The article deals with the organization of studying psychological and pedagogical subjects for students of technical universities.